Two new needle-shaped Nitzschia taxa from a deep East African crater lake. Issue 4 (2nd October 2017) - Cocquyt, Christine; Ryken, Els
Abstract : Two new diatoms, Nitzschia fabiennejansseniana Cocquyt & Ryken sp. nov. and Nitzschia pseudoaequalis Cocquyt sp. nov., are described from Lake Challa, a deep crater lake in East Africa, based on light and electron microscopical observations. These Nitzschia species are morphologically similar to other needle-shaped, planktonic Nitzschia present in freshwater lakes of tropical Africa. The differences between the newly described species and related Nitzschia taxa are a combination of the shape of the poles, the number of striae and fibula in 10 µm, and the presence of a central gap between the fibulae. Nitzschia fabiennejansseniana is common in the plankton of Lake Challa towards the end of the main dry and windy season during the northern hemisphere summer, when deep water-column mixing causes upwelling of nutrient-rich hypolimnetic water. Together with Afrocymbella barkeri, this taxon is the dominant diatom in the pelagic phytoplankton of Lake Challa today, and has been continuously over at least the last several hundreds of years, as recorded in its sediments. The temporal dynamics of both taxa in Lake Challa play a major role in the interpretation of past climate change in equatorial East Africa. The other new taxon, N. pseudoaequalis, was common in some epilithic samples taken from the littoral zone of Lake Challa. It was also sporadically observed in the pelagic phytoplankton near the end of the mixing season.